Rană și dor în relația omului cu Dumnezeu (Verbum. Revista de teologie catolică, 2025)
This study intends to explore the relationship between man and divinity from a metaphysical perspective, following the ascending road of the human soul to-wards God and, afterwards, from a theological descending perspective by analysing the role of divine grace in restoring the wounded relationship. The concepts of wound and wistfulness, extracted from the lexical field of emotions, are analysed more as generating existential seeking and a self-analysis of the spirit that perceives its own itinerary towards meaning, going beyond the absurd born out of the sentiment of human capabilities ever so limited when striving to reach the intangible and to comprehend the incomprehensi-ble. We bring into discussion the feminine language of love in relation to the absolute alterity. We analyse concrete forms of social charity.
Keywords: love; wound; wistfulness; relationship; alterity; feminine language; social charity